2013
DOI: 10.1177/0148607113496118
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite and Nitrate Concentrations and Metabolism in Breast Milk, Infant Formula, and Parenteral Nutrition

Abstract: Dietary nitrate and nitrite are sources of gastric NO, which modulates blood flow, mucus production, and microbial flora. However, the intake and importance of these anions in infants is largely unknown. Nitrate and nitrite levels were measured in breast milk of mothers of preterm and term infants, infant formulas, and parenteral nutrition. Nitrite metabolism in breast milk was measured after freeze-thawing, at different temperatures, varying oxygen tensions, and after inhibition of potential nitrite-metaboliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 52 publications
1
19
1
2
Order By: Relevance
“…This is true regardless of whether they are receiving breast milk, artificial milk, or parenteral nutrition (810). Based on a breast milk intake of 150ml/kg/day and our measurements of nitrate and nitrite concentrations (13 and 0.13 μmol/l, respectively), we have estimated that infants ingest approximately 0.12ml/kg/day of nitrate and 0.0007 ml/kg/day of nitrite from fresh breast milk, which equates to only 5% and 0.6% of the nitrate and nitrite intake of adults (10). A comparison of the average dietary nitrate intake in newborn infants and adults is shown in Figure 2.…”
Section: Dietmentioning
confidence: 99%
See 4 more Smart Citations
“…This is true regardless of whether they are receiving breast milk, artificial milk, or parenteral nutrition (810). Based on a breast milk intake of 150ml/kg/day and our measurements of nitrate and nitrite concentrations (13 and 0.13 μmol/l, respectively), we have estimated that infants ingest approximately 0.12ml/kg/day of nitrate and 0.0007 ml/kg/day of nitrite from fresh breast milk, which equates to only 5% and 0.6% of the nitrate and nitrite intake of adults (10). A comparison of the average dietary nitrate intake in newborn infants and adults is shown in Figure 2.…”
Section: Dietmentioning
confidence: 99%
“…We have also shown that nitrite is oxidized to nitrate in breast milk by an enzyme normally present in milk, lactoperoxidase, leading to even lower levels in milk that has been allowed to sit at room temperature or which has been freeze-thawed (10). Breast milk nitrite concentrations also fall during the first few weeks of life, with the highest levels found in colostrum and decreasing to nearly undetectable amounts in milk collected after the third week postpartum (9,10).…”
Section: Dietmentioning
confidence: 99%
See 3 more Smart Citations